Mapping root zone soil moisture using remotely sensed optical imagery - Scott, Christopher A.; Bastiaanssen, Wim G.M.; Ahmad, Mobin-ud-Din (2003)
Field-based soil moisture measurements are cumbersome. Remote sensing techniques based on active or passive microwave data have limitations. This paper presents and validates a new method based on land surface energy balances using remotely sensed optical data (including thermal infrared),